EXPERIMENTAL ANIMAL MODELS FOR ALZHEIMER DISEASE - (:unkn) unknown (NOBEL ILAC, 2018)
Alzheimer's disease (AD) which is an age related disorder is characterized by progressive cognitive decline. Accumulation of extracellular amyloid plaques, intracellular neurofibrillary tangles and neuronal loss is observed in AD brain. Exploring the neuropathology of AD in human pre-clinical stages is not easy. Mechanisms which causes AD in preclinical stage and potential new therapeutic targets are understood by transgenic animal models. McGill-R-Thy1-APP rat model is the only model to reproduce AD-like amyloid pathology with a single transgene. A beta has been the most cited probable causative factor in the onset and progression of AD. In A beta-based rodent models, there is a significant correlation between increased A beta levels and cognitive decline. Risk genes in the development of AD are amiloid precursor protein (APP), presenilin-1 (PS-1), presenilin-2 (PS-2) which contain autosomal dominant mutations. In rat models of Tau pathology, transgenic rats which overexpress mutant APP/PS1 display increased Tau alterations in the brain. Injection of A beta into rat brain is an alternative AD animal model to the use of transgenic animals. In this model, after A beta 1-42 is injected into the CA3 region of hippocampus, progressive decline in behavioral responses are observed. Despite the large variety of therapeutic approaches, AD remains incurable. Because, in clinical diagnosis stage, the brain has suffered irreversible and extensive damage.
Keywords: Alzheimer; amyloid beta eta; neurofibrillary tangles; Tau; transgenic animal models; INSULIN; TAU